2020
DOI: 10.1021/acsomega.9b03586
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitrogen on the Porosity, Surface, and Electrochemical Characteristics of Activated Carbon

Abstract: Surface functionalities of activated carbon can be affected by the presence of heteroatoms such as oxygen, sulfur, and nitrogen. In this work, nitrogen-doped activated carbons (NACs) were prepared from shrimp shells, and the effects of the mixing ratio (raw material to an activating agent) on the porous texture and surface functionalities were investigated. It was found that, with increasing the mixing ratio (resulting in increasing N/C), the development of mesoporosity was significantly observed. This led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…However, the excessive amounts of N content can collapse the pore structure, which results in conversion of micropores into mesopores, thereby leading to loss of surface area. 54 Arenillas et al suggested that at high nitrogen content, the edges of graphene layers may be heavily decorated by the N-functional groups, which act as steric obstacles and partly block the nitrogen to pores, leading to a decrease in surface area. 55 Therefore, the surface area increases from NAC (1:1) to NAC (2:1) and further declines in the case of NAC (3:1).…”
Section: Resultsmentioning
confidence: 99%
“…However, the excessive amounts of N content can collapse the pore structure, which results in conversion of micropores into mesopores, thereby leading to loss of surface area. 54 Arenillas et al suggested that at high nitrogen content, the edges of graphene layers may be heavily decorated by the N-functional groups, which act as steric obstacles and partly block the nitrogen to pores, leading to a decrease in surface area. 55 Therefore, the surface area increases from NAC (1:1) to NAC (2:1) and further declines in the case of NAC (3:1).…”
Section: Resultsmentioning
confidence: 99%
“…The prepared monomer was stated for organic electronics ( Treeweranuwat et al, 2020 ). Therefore, the network polymers prepared using the monomer can be highly conductive in nature.…”
Section: Resultsmentioning
confidence: 99%
“…The precursors for the preparation of AC usually contain carbon, such as coals , and coconut shells . Their adsorption capacity, wettability, and ion storage capacity can be enhanced by introducing heteroatoms such as nitrogen, oxygen, and sulfur into the carbon skeleton. Heteroatoms are usually introduced into the carbon framework of ACs by the following approaches: (i) post-treatment of ACs by chemical reactions with reagents containing the desired heteroatoms, (ii) molecular grafting of heteroatoms onto the carbon framework, and (iii) carbonization and activation of heteroatom-rich carbonaceous materials . Chemical impregnation with a chemical agent such as ZnCl 2 , H 3 PO 4 , and KOH can prevent tar formation and enhance carbon conversion.…”
Section: Introductionmentioning
confidence: 99%